Radiotherapy plus camrelizumab affects peripheral CD8 T-cell differentiation subsets expressing PD-1, TIGIT, and CTLA-4 in esophageal squamous cell carcinoma. Issue 1 (10th January 2023) - Guo, Zhoubo; Zhang, Kunning; Wei, Xiaoying; Li, Yanqi; Ma, Xiaoxue; Li, Yang; Han, Dong; Du, Qingwu; Zhang, Tian; Chen, Xi; Wei, Hui; Yan, Cihui; et al.
Abstract: Our previous phase Ib trial (NCT03222440) showed that radiotherapy plus the anti–PD-1 antibody camrelizumab is a safe and feasible first-line therapy for locally advanced esophageal squamous cell carcinoma. In this study, we divided peripheral CD8 T-cell differentiation subsets into 4 subpopulations (naive T cells, central memory T cells, effector memory T cells, and CD45RA + effector memory T cells). We then investigated the influence of radiotherapy plus camrelizumab therapy on the proportions of the 4 subsets and their PD-1, TIGIT, and CTLA-4 expression as well as their proliferative activity and compared the effects with those of concurrent chemoradiotherapy. Nineteen and 15 patients with esophageal squamous cell carcinoma who received radiotherapy plus camrelizumab therapy and concurrent chemoradiotherapy, respectively, were enrolled in this study. We isolated peripheral blood mononuclear cells from these patients before treatment and longitudinally after the delivery of 40 Gy radiotherapy. Flow cytometry was conducted to detect peripheral CD8 T-cell subsets and PD-1, TIGIT, CTLA-4, and Ki67 expression levels in patients with esophageal squamous cell carcinoma. We found that radiotherapy plus camrelizumab therapy did not change the proportions of the 4 subsets or the expression of CTLA-4, but this therapy decreased PD-1 expression by the 4 subsets and TIGIT expression by effector memory T cells, as well as significantly enhanced the proliferative activity of CD8 T cells, whereas concurrent chemoradiotherapy produced different effects. In addition, we further identified peripheral biomarkers that potentially predict the outcome of radiotherapy plus camrelizumab therapy. Abstract : This study reviews changes of the peripheral CD8 T-cell subpopulation expressing PD-1, TIGIT, and CTLA-4 mediated by radiotherapy plus camrelizumab and concurrent chemoradiotherapy.